THE TRADITION OF EARLY MARRIAGE IN RURAL AND MOUNTAINOUS AREAS: A CASE STUDY IN BETEK VILLAGE, KRUCIL DISTRICT, PROBOLINGGO REGENCY - Samsul Arifin (International Journal of Multidisciplinary Reseach, 2025)
This study examines the persistence of early marriage as a socio-religious tradition in Betek Village, Krucil District, Probolinggo Regency, Indonesia. Despite the enactment of Law No. 16 of 2019, which sets the minimum marriage age at 19, early marriage continues to be practiced as part of local cultural identity. Employing a qualitative field research approach with a socio-legal perspective, this study explores how Islamic legal norms intersect with local customs and socio-economic realities. Data were collected through in-depth interviews, observations, and documentation involving religious leaders, community elders, young couples, and local authorities. The findings reveal that early marriage is perceived by villagers as a moral and social obligation to preserve family honor and prevent social deviance. However, the practice often leads to economic vulnerability, limited educational attainment, and psychological strain among young couples. From the perspective of maqāṣid al-sharī‘ah, early marriage tends to generate more harm than benefit, undermining the principles of welfare, intellect, and lineage protection. The study concludes that a contextual reinterpretation of Islamic law, combined with education and community engagement, is essential to transform early marriage traditions toward more just and welfare-oriented practices in accordance with Islamic family ideals.